2019
DOI: 10.1002/anie.201909843
|View full text |Cite
|
Sign up to set email alerts
|

Coordinative Chain Transfer Polymerization of Butadiene with Functionalized Aluminum Reagents

Abstract: Functionalized aluminum alkyls enable effective coordinative chain transfer polymerization with selective chain initiation by the functionalized alkyl. (ω‐Aminoalkyl)diisobutylaluminum reagents (12 examples studied) obtained by hydroalumination of α‐amino‐ω‐enes with diisobutylaluminum hydride promote the stereoselective catalytic chain growth of butadiene on aluminum in the presence of Nd(versatate)3, Cp*2Nd(allyl), or Cp*2Gd(allyl) precatalysts and [PhNMe2H+]/[B(C6F5)4 −]. Carbazolyl‐ and indolylaluminum rea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(13 citation statements)
references
References 28 publications
0
13
0
Order By: Relevance
“…Mecking et al reported on functionalized aluminum alkyls, which are capable of selective polymerization via coordinative chain transfer. 89 In this regard, functionalized and easily accessible mixed 77 that a large number (~90%) of aluminum-bound carbazole groups are able to initiate polymerization while retaining high (90-95%) cis-1,4 butadiene.…”
Section: E Nickel Catalystsmentioning
confidence: 99%
“…Mecking et al reported on functionalized aluminum alkyls, which are capable of selective polymerization via coordinative chain transfer. 89 In this regard, functionalized and easily accessible mixed 77 that a large number (~90%) of aluminum-bound carbazole groups are able to initiate polymerization while retaining high (90-95%) cis-1,4 butadiene.…”
Section: E Nickel Catalystsmentioning
confidence: 99%
“…Sita et al also reported CCTP reactions of propylene to afford atactic PP with tunable molecular weights (although the M n for i PP was only 1000–2000) and very narrow Poisson molecular weight distributions (PDI < 1.2). ,, The absolute cost of CCTP is lower than that of ordinary living coordinative polymerization (LCP): CCTP circumvents the critical “one polymer chain per metal center” of LCP, which has proven to be an insurmountable liability for the large-scale production of precision polyolefins. In principle, CCTP offers great potential for large-scale production of low-molecular-weight, end-functionalized polyolefins and, more importantly, high-molecular-weight, well-controlled linear block copolymers.…”
Section: Introductionmentioning
confidence: 99%
“…Within conventional free-radical polymerisation of vinyl monomers the telogen is often referred to as a chain-transfer agent (CTA) and the structure, chemistry and concentration of the chosen CTA has a significant influence on polymerisation outcomes; 21 a range of CTA strategies have been reported including addition of compounds such as thiols, coordinative chain transfer, 22 the use of cobalt-derived catalytic chain transfer. 23 Strictly speaking, the CTA is only considered a telogen if very short chains are formed, comprising chain-ends that are derived solely from the CTA, 24 and initiator residues are not found within the oligomeric product.…”
Section: Introductionmentioning
confidence: 99%